Quality of Life and Limb Functionality in Adolescents and Young Adults Surviving Bone Tumors in the Lower Extremity in a Developing Country: A Cross-Sectional Study - Vasquez, Liliana; Tello, Mariela; Maza, Ivan; Shah, Darshi; Silva, Jose; Sialer, Luis (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Due to higher survival rates among patients with bone tumors, there is a growing interest in determining these individuals' limb functionality and psychosocial prognosis.Objectives This study aimed to analyze the differences in functionality and quality of life (QoL) related to health in patients diagnosed with a malignant bone tumor during childhood, according to the type of surgery performed.Materials and Methods A cross-sectional study was performed for patients older than 14 years who treated for osteosarcoma or Ewing's sarcoma of the lower limb by who receiving surgery. To assess lower limb functionality and QoL among patients surviving malignant bone tumors, 19 patients surviving osteosarcoma or Ewing's sarcoma of the lower extremity were studied. An evaluation of functionality and QoL was done using the “Enneking and Medical Outcomes Study Short-Form 36 scales.” We compared the functional results according to the surgical technique used. Categorical variables were compared according to the Mann–Whitney and Kruskal–Wallis tests, with an established 95% level of significance.Results QoL among patients who had conservative surgery was not significantly better than amputee patients in the physical or mental aspects, nor in any of their components. Limb functionality, according to Enneking's staging, was significantly higher in non-amputee patients (p = 0.035).Conclusion According to the data analysis done in this study, the QoL was found to be not significantly different, based on the type of surgery performed; however, there were differences in limb functionality.
Keywords: survivorship; quality of life; osteosarcoma; Ewing's sarcoma